Bibliometric Evaluation of Open Access Publishing in Intellectual Property Rights - Febryani, Evy; Lubis, Arief Fahmi (Eastasouth Institute, 2024)
This study conducts a bibliometric evaluation of open access publishing in the realm of intellectual property rights (IPR), aiming to provide insights into the landscape, trends, and potential research directions within this domain. Utilizing data spanning from 1970 to 2024, encompassing 1000 papers with 9684 citations, the analysis employs network visualization, cluster analysis, and trend examination techniques. The results highlight the collaborative nature of scholarly endeavors in IPR, with key themes emerging around the economic implications of IPR, its intersection with global trade, biotechnology, and human rights. These findings offer valuable insights for researchers, policymakers, and practitioners, facilitating evidence-based decision-making and promoting transparency and accessibility in the dissemination of IPR-related knowledge.